Physical-Recreational Games to Increase the Participation of Children in the Recreational Activities of the Bengochea District - Hernández Moya, Rosa de la Cruz; Pacheco Rodríguez, Ernesto (My University, 2021)
The present investigation deals with the use of recreational physical games aimed at increasing the participation of boys from 9 – 12 years old in district # 9 of the Bengochea district, Santa Clara municipality, to recreational physical activities; for this, we start with the current diagnosis of participation in activities, based on the interests, tastes and preferences the boys, since passive entertainment has become widespread due to the marked fondness for video games, the use of tablets, computers, smartphones, among others. In order to explore the researched topic, different scientific and technical methods were used that allowed to consult bibliographies of several authors, national and foreign, this allowed to make the selection and evaluation of the implementation of ten physical recreational games, where the boys recognized the benefits of to realize active games, besides the acceptance and impact of these games, before the passive activities that they realized in their free moments.
Keywords: Recreational physical games; Recreational activities